Samtal med vinden: Kulturforskning i lufthavet - Arvastson, Gösta (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2015)
Unlike other ethnographic objects, it is impossible to put a label on the wind. Air and winds are everywhere and transcend time and place. The “new meteorology” became an international movement in the late 19th century. Cooperation between countries was a necessity. There were clear similarities with the dream of one world in which peoples spoke the same language, the wars were over and the “narrow-minded nations” dissolved. In this sense, a world culture became realized in a limited field. The original ideas of a world culture ended in street riots during the bloody days of June, 1848. The article concludes with some remarks on today’s climate debate.